Maximum Entropy Variational Approach to Collective States - Canosa, Norma Beatriz (1993)
An approximation to the energy eigenstates of a many-body system, based on a previously introduced maximum entropy approach to the ground state, is developed and applied to a monopole fermion system. An excellent agreement with the exact eigenstates is obtained over the whole range of the pertinent coupling constant.